TANTANGAN IMPLEMENTASI SISTEM INFORMASI MANAJEMEN DI ERA DIGITAL - Ririn Arianti Harahap; Muhammad Irwan Padli Nasution (INTERNATIONAL, Journal of Sharia Business Management, 2025)
The challenges of implementing Manajemen Information System in the digital era are increasingly complex with thke rapid development of information technology. Various obstacles arise, such as limited technologically literate human resources, diffiiculties integrating legacy and new system, high implementation costs, resistance to change, and data security and privacy issue. Meanwhile, technological advances such as cloud computing, artificial intelligencel, and big data analytics require organizations to continuously adapt and improve their digital competencies. The success of Manajemen Information System implementation depends heavily on leadership support, ongoing training, and effective change management. Through proper implementation, Management Information Systems can improve operational efficiency, data accuracy, and decision-making quality, while strengthening organizational competitiveness amidst the ever-evolving digital transformation.